Colorectal cancer-associated Streptococcus infantarius subsp. infantarius differ from a major dairy lineage providing evidence for pathogenic, pathobiont and food-grade lineages - (:unkn) unknown (My University, 2018)
Streptococcus infantarius subsp. infantarius (Sii), a member of the Streptococcus bovis/Streptococcus equinus complex (SBSEC), predominates as dairy-adapted and non-adapted variants in fermented dairy products (FDP) in East and West Africa. Epidemiologic data suggest an association with colorectal cancer for most SBSEC members, including Sii from Kenyan patients. Phylogenetic relationships of East African human (EAH) isolates to those of dairy and pathogenic origin were analysed to better estimate potential health implications via FDP consumption. The MLST-derived population structure was also evaluated to provide host, disease, geography and dairy adaptation associations for 157 SBSEC isolates, including 83 novel Sii/SBSEC isolates of which 40 originated from Kenyan colonoscopy patients. Clonal complex (CC) 90 was delineated as potential pathogenic CC for Sii. Single EAH, West African dairy (WAD), food and animal Sii isolates clustered within CC-90, suggesting a potential link to pathogenic traits for CC-90. The majority of EAH and WAD Sii were clustered in a shared clade distinct from CC-90 and East African dairy (EAD) isolates. This indicates shared ancestry for the EAH and WAD clade and limitations to translate disease associations of EAH and CC-90 to EAD Sii, which could support the separation of pathogenic, pathobiont/commensal and food lineages.
Keywords: African Research